A gigantically increased ratio of electrical to thermal conductivity and synergistically enhanced thermoelectric properties in interface-controlled TiO2–RGO nanocomposites. Issue 23 (30th May 2017) - Nam, Woo Hyun; Lim, Young Soo; Kim, Woochul; Seo, Hyeon Kook; Dae, Kyun Seong; Lee, Soonil; Seo, Won-Seon; Lee, Jeong Yong
Abstract : A strategy of interface control using reduced graphene oxide is proposed for the enhancement of thermoelectric properties. Abstract : We report synergistically enhanced thermoelectric properties through the independently controlled charge and thermal transport properties in a TiO2 –reduced graphene oxide (RGO) nanocomposite. By the consolidation of TiO2 –RGO hybrid powder using spark plasma sintering, we prepared an interface-controlled TiO2 –RGO nanocomposite where its grain boundaries are covered with the RGO network. Both the enhancement in electrical conductivity and the reduction in thermal conductivity were simultaneously achieved thanks to the beneficial effects of the RGO network, and detailed mechanisms are discussed. This led to the gigantic increase in the ratio of electrical to thermal conductivity by six orders of magnitude and also the synergistic enhancement in the thermoelectric figure of merit by two orders. Our results present a strategy for the realization of 'phonon-glass electron-crystals' through interface control using graphene in graphene hybrid thermoelectric materials.